Voltage pulse formation for energizing the magnetron gun with a secondary-emission cathode - Chertishchev, I.A.; Reshetnyak, N.G.; Romas’ko, V.P.; Zakutin, V.V. (Вопросы атомной науки и техники, 2014)
Various techniques have been investigated for forming a high-voltage pulse to energize magnetron guns with secondary-emission cathodes. To generate a powerful beam, it was necessary that the storage element in the modulator should have a low wave impedance. A capacitor and a low-impedance forming line were used as a storage element. The flat part of the pulse was formed by means of different correction circuits. The influence of correction circuit elements on the pulse form has been investigated. Consideration has been given to the circuits of spike control by means of the driving generator, and also, by including the correction circuits in the discharge circuit. Spike formation through the use of pulse-transformer parasitic parameters was also considered. The undertaken studies have demonstrated the possibility of creating a modulator for energizing the accelerator with electron energy up to 150 keV. Исследованы различные возможности формирования высоковольтного импульса напряжения для питания магнетронных пушек с вторично-эмиссионными катодами. Для получения мощного пучка необходимо, чтобы накопительный элемент в модуляторе имел малое волновое сопротивление. В качестве накопительного элемента использовались конденсатор и низкоомная формирующая линия. Плоскую часть импульса формировали при помощи различных корректирующих цепочек. Рассмотрено влияние элементов корректирующих цепочек на форму импульса. Рассмотрены схемы регулировки выброса при помощи затравочного генератора и при включении цепей коррекции в разрядный контур, а также формирование выброса за счет паразитных параметров импульсного трансформатора. Проведенные исследования показали возможность создания модулятора для питания ускорителя с энергией электронов до 150 кэВ. Досліджені різні можливості формування високовольтного імпульсу напруги для живлення магнетронних гармат з вторинно-емісійними катодами. Для здобуття потужного пучка необхідно, щоб накопичувальний елемент у модуляторі мав малий хвильовий опір. В якості накопичувального елемента використовувалися конденсатор або низькоомна формуюча лінія. Плоску частину імпульсу формували за допомогою різних корегуючих ланцюгів. Розглянуто вплив елементів корегуючих ланцюгів на форму імпульсу. Розглянуто схеми регулювання викиду напруги за допомогою затравочного генератора та при включенні ланцюгів корекції у розрядний контур, а також за рахунок паразитних параметрів імпульсного трансформатора. Проведені дослідження показали можливість створення модулятора для живлення прискорювачів з енергією електронів до 150 кеВ.